2021
DOI: 10.4253/wjge.v13.i8.238
|View full text |Cite
|
Sign up to set email alerts
|

Six intragastric balloons: Which to choose?

Abstract: Endoscopically placed intragastric balloons (IGBs) have played a significant role in obesity treatment over the last 30 years, successfully bridging the gap between lifestyle modification/pharmacotherapy and bariatric surgery. Since they provide a continuous sensation of satiety that helps the ingestion of smaller portions of food, facilitating maintenance of a low-calorie diet, they have generally been considered an effective and reversible, less invasive, non-surgical procedure for weight loss. However, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 96 publications
0
27
0
4
Order By: Relevance
“…After decades of development, IGB devices are now more effective, safe, and less traumatic than ever before while maintaining the benefits of reversibility and without altering the anatomy of the gastrointestinal system [12] . IGBs are associated with a lower mortality (<1%), long-lasting, effective excess weight loss (EWL) percentage greater than 50%, fewer adverse effects, reversible and reproducible, and good quality of life [13] . However, Italian research revealed that BioEnterics intragastric balloon (BIB®) therapy for 14 months provided greater results with higher weight reduction than BIB® in situ within 6 months without complications [14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After decades of development, IGB devices are now more effective, safe, and less traumatic than ever before while maintaining the benefits of reversibility and without altering the anatomy of the gastrointestinal system [12] . IGBs are associated with a lower mortality (<1%), long-lasting, effective excess weight loss (EWL) percentage greater than 50%, fewer adverse effects, reversible and reproducible, and good quality of life [13] . However, Italian research revealed that BioEnterics intragastric balloon (BIB®) therapy for 14 months provided greater results with higher weight reduction than BIB® in situ within 6 months without complications [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Here, our patient had a silicone saline balloon which should stay for 6 months inside the stomach, as suggested earlier by Buzga et al [15] . These spherical IGBs allow the addition or removal of saline in situ, allowing patients to customize their intragastric volume to fit their weight loss goals and preferences [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the detailed analysis of related publications covering two decades could help to identify changes occurring in scienti c trends over this period [24]. It has thus become clear that many centers with longterm experience with the Orbera balloon consider it trustworthy and reliable, and are disinclined to change just for the sake of a study [4]. On the other hand, new physicians in this era, or new markets, as big as the USA or as small as the Czech Republic, are trying the more modern balloons.…”
Section: Discussionmentioning
confidence: 99%
“…The advantageous results of the method, its simplicity, and the relatively low cost of the device, are clearly re ected not only in its growing worldwide popularity, but mainly in the expansion of technological research towards improvement of the "classic" uid-lled balloon, which, for more than a decade, has been the absolute status [4] and has the most historical data supporting its use.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a significant threat to human health owing to the high prevalence of morbidity and mortality caused by the cdition itself and associated comorbidities [1]. Current guidelines suggest bariatric surgery as the most potent treatment tool for patients with class-3 obesity or those with class-2 obesity compounded by an obesity-related comorbidity [2][3][4].…”
Section: Introductionmentioning
confidence: 99%